2019
DOI: 10.1002/lary.28066
|View full text |Cite
|
Sign up to set email alerts
|

The impact of the multidisciplinary tumor board on head and neck cancer outcomes

Abstract: Objectives/Hypothesis Although the multidisciplinary tumor board (MTB) is accepted as best practice for the management of head and neck squamous cell carcinoma (HNSCC), there is limited evidence showing its impact on survival. Our goal was to investigate the impact of an MTB following the hiring of a fellowship‐trained head and neck surgeon and implementation of an MTB at our institution. We hypothesized that these changes would demonstrate an improvement in survival. Study Design Retrospective chart review. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
63
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 74 publications
(68 citation statements)
references
References 20 publications
3
63
0
2
Order By: Relevance
“…There is strong evidence to suggest that MDC implementation may improve pretreatment evaluation (dental, nutrition), 6 proper staging, 7,8 and appropriate timely treatment 6‐11 . It may also affect disease specific survival 11,12 and overall survival 10‐15 but this is controversial. As MDC usage has become more widespread, academic institutions are beginning to evaluate MDC quality measures with respect to guideline adherence and patient outcomes 13 .…”
Section: Utility Of a Multi‐disciplinary Team Conferencementioning
confidence: 99%
“…There is strong evidence to suggest that MDC implementation may improve pretreatment evaluation (dental, nutrition), 6 proper staging, 7,8 and appropriate timely treatment 6‐11 . It may also affect disease specific survival 11,12 and overall survival 10‐15 but this is controversial. As MDC usage has become more widespread, academic institutions are beginning to evaluate MDC quality measures with respect to guideline adherence and patient outcomes 13 .…”
Section: Utility Of a Multi‐disciplinary Team Conferencementioning
confidence: 99%
“…Multidisciplinary care through a head and neck tumor board has been clearly shown to improve outcomes in patients with head and neck cancer. [16][17][18] During the COVID-19 pandemic, utilization of a multidisciplinary decision-making is of critical importance, especially when there is an influx of many patients during a time of limited resources and high risk of COVID-19 transmission. In some situations, surgical and nonsurgical treatment options may have similar outcomes.…”
Section: Strategies To Mitigate the Hnc Surgementioning
confidence: 99%
“…He stated the need of an interdisciplinary education of head neck surgeons:" This is the only way that the future 'multidisciplinary team' will have not merely head and neck surgeons, but rather head and neck surgical oncologists as members; that is what I hope the guidelines come to reflect in years to come" (37). Recently Liu et al (38) demonstrated that multidisciplinary tumor boards have a positive impact on head and neck cancer patient outcome, but further literature addressing questions of best practice in this field is lacking.…”
Section: What Is "Best Practice" In Head and Neck Surgery: Upper Aeromentioning
confidence: 99%